Improvement of oral efficacy of Irinotecan through biodegradable polymeric nanoparticles through in vitro and in vivo investigations. (19th May 2018) - Ahmad, Niyaz; Alam, Md Aftab; Ahmad, Rizwan; Umar, Sadiq; Jalees Ahmad, Farhan
Abstract: Background: Irinotecan (IRN) (CPT-11) is a camptothecin derivative with low oral bioavailability due to active efflux by intestinal P-glycoprotein (p-gp) receptors. Hence, no oral formulation is marketed for IRN till date and its oral ingestion continues to remain a challenge. Aim of study: The study aims to develop a nanoformulation i.e. Chitosan (CS)-coated-IRN-loaded-poly-lactic-co-glycolic acid (PLGA) nanoparticles (NPs) (CS-IRN-PLGA-NPs)in order to enhance oral bioavailability of IRN. Results: Developed formulation revealed particle size, 166.9 ± 13.63 nm, zeta potential, 14.67 ± 1.08 mV and drug content (42.69 ± 1.97 µg/mg), with spherical shape and smooth surface. Cytotoxicity studies, performed against human breast adenocarcinoma cell lines (MCF-7), confirmed the superiority of IRN-CS-PLGA-NPs over free IRN solution (IRN-S). Cellular transport conducted on human colon adenocarcinoma cell line (Caco-2) exhibited a higher permeability of 1.33 folds for IRN through CS-IRN-PLGA-NPs as compared to IRN-S ( p  < 0.01) whereas the permeability for IRN was found to be higher at a rate of 4.32 folds, across rat ileum. Furthermore, pharmacokinetic studies demonstrated marked improvement of 3.53 fold and 8.03 fold in Wistar rat's plasma as well as brain higher oral bioavailability through IRN-CS-PLGA-NPs when compared with IRN-S. A simple, rapid UPLC-ESI-Q-TOF-MS/MS method for the determination of IRN (CPT-11) and SN-38 in both plasma and brain (over a range: 1.00–25000.00 ng/ml) was also developed and successfully applied for pharmacokinetic study. Discussion: CS-IRN-PLGA-NPs approach may be effectively utilised, to replace pre-existing intravenous therapy thus providing 'patient care at home. Abstract :